The Difference in the Effects of Static and Dynamic Core Training Programs on Soccer Skills in Terms of Motor Performance (An Experimental Study on Male - Farhan Firmansyah; Sapta Kunta Purnama; Haris Nugroho (CV. Creative Tugu Pena, 2025)
This study aimed to determine: (1) the difference in the effects between static and dynamic core training programs on soccer skills, (2) the difference in soccer skills between athletes with high and low motor performance, and (3) the interaction between training programs and motor performance on soccer skills. This study employed an experimental method with a 2 × 2 factorial design. The population consisted of 27 male players from SSB Watuska Surakarta, with a sample of 24 players selected using purposive sampling and grouped based on the extreme groups design principle. The research instruments included motor performance tests and soccer skill tests, which were standardized using T-scores. Data analysis was conducted using a two-way ANOVA test with a significance level of α = 0.05, followed by pairwise comparison tests. The results showed that: (1) there was no significant difference in the effect between static and dynamic core training programs on soccer skills (p = 0.627 > 0.05), with a small effect size (η² = 0.012); (2) there was a significant difference between players with high and low motor performance (p = 0.023 < 0.05), with a large effect size (η² = 0.234), where the low motor performance group demonstrated substantially greater improvement in soccer skills compared to the high motor performance group; and (3) there was no significant interaction between training program and motor performance level on soccer skills (p = 0.706 > 0.05). The conclusion of this study indicates that the effectiveness of core training is more influenced by the individual’s initial motor performance capacity rather than the type of training method. Core training is highly effective for players with stability deficits (low motor performance), but it must be applied carefully in players with high motor performance to avoid overload, which may lead to increased muscle stiffness and reduced movement elasticity.